Velocity - Koontz, Dean R. (Dean Ray), 1945- (New York : Bantam Books, 2005)
A series of communications from a deranged killer in which he is offered a number of devastating choices and deadlines draws Bill Wile into a confrontation with pure evil.
Accelerated Reader AR
Keywords: Serial murders -- Fiction; Psychopaths -- California -- Napa County -- Fiction; Bartenders -- Fiction; Police -- California -- Napa County -- Fiction; Napa County (Calif.) -- Fiction; Psychological fiction; Suspense fiction